Students’ Awareness of Reproductive Health and Learning Achievment in Problem Based Learning Syntax Assisted with Facebook - Afifah, Nuryatul; Prasetyo, Andreas Priyono Budi; Widiyaningrum, Priyantini (Journal of Biology Education, 2018)
Learning Biology on subject of reproductive system often only emphasizes biological aspects rather than reproductive health education aspects. This study aims to identify the effect of problem based learning (PBL) assisted with Facebook on learning achievment, reproductive health awareness, and the relationship of learning achievment with reproductive health awareness. The design of this research is quasi experiment with non-equivalent control group design pattern. The population is all students of class XI IPA SMA Negeri 1 Jakenan. This research used purposive sampling technique obtained from class XI IPA 2 (40 students) as experiment group and XI IPA 3 (42 students) as control group. The implementation of learning is measured by observation sheet and student responses to learning activities. The score of learning result obtained through posttest. The awareness of reproductive health is measured through the scale of reproductive health awareness. The data of this research were analyzed quantitatively with the help of Ms.Excel software and SPSS version 23. The results showed that PBL that assisted with Facebook had a significant effect on learning achievment and students awareness of reproductive health. According to the correlation test, there is a very strong positive relationship between student learning achievment and students' awareness of reproductive health.